Penggunaan Media Digital Sebagai Sarana Promosi Potensi Wisata Di Kelurahan Alun-Alun Contong - Alfin Fitra Perdana; Fauzatul Laily Nisa; Marseto Marseto (LPPM Universitas Dharma Andalas, 2022)
Most people make cell phones a necessity. Of course this can be used as a means of promotion, namely through digital media. In the Alun-Alun Contong Village, there are several spots that are quite historic and are still well maintained, such as: the HBNU office, the tomb of Kyai Sedo Masjid, the tomb of Prince Pekik, the tomb of Joko Jumput, and several houses that have existed since the colonial era. The obstacle related to the potential in Contong Alun-Alun Village is the lack of information & promotion that can reach the wider community. For this reason, it is necessary that contains tourism potential on digital media, so that it can be reached by all people and make tourism more well known. This study uses a descriptive qualitative approach with data collection techniques via the internet, direct surveys, and interviews. The existence of tourism content can help increase public awareness. So that people are interested and visit the Contong Square area and can improve the economy of the surrounding community through tourism and the MSMEs involved.